Quercus ilex Extract Ameliorates Acute TNBS-Induced Colitis in Rats - Castejón, Maria Luisa; Rosillo, Maria Ángeles; Villegas, Isabel; Sánchez-Hidalgo, Marina; Hadidi, Lila; Zaidi, Farid; Alarcón-de-la-Lastra, Catalina (Planta Medica, 2019)
Quercus ilex L. (Fagaceae) is one of the most commonly used plants in folk medicine in the Mediterranean region to treat gastrointestinal disorders. The aim of the present study was to evaluate the effects of a polyphenol extract from mature leaves of Q. ilex on acute 2,4,6-trinitrobenzene sulfonic acid-induced colitis in rats. A polyphenol extract from mature leaves of Q. ilex (250 and 500 mg/kg/day) was administered by gavage 48, 24, and 1 h prior to the induction of colitis with 2,4,6-trinitrobenzene sulfonic acid as well as 24 h later. The inflammation response was assessed by histology, myeloperoxidase activity, and Th1 proinflammatory cytokine production. The protein expression of cyclooxygenase-2 and inducible nitric oxide synthase, and signaling pathways were studied by Western blotting in the colon tissues. The polyphenol extract from mature leaves of Q. ilex decreased neutrophil infiltration, interleukin-1β and TNF-α production, and proinflammatory proteins cyclooxygenase-2 and inducible nitric oxide synthase overexpression. Also, the polyphenol extract from mature leaves of Q. ilex was capable of blocking the activation of mitogen-activated protein kinases and nuclear transcription factor-kappa B. Furthermore, the reduction of inflammation by polyphenol extract from mature leaves of Q. ilex treatment was accompanied by a recovery of Nrf2 and heme oxygenase-1 protein expression levels. In conclusion, this study demonstrates that a polyphenol extract from mature leaves of Q. ilex improves 2,4,6-trinitrobenzene sulfonic acid-induced colitis, probably through mitogen-activated protein kinase/nuclear transcription factor-kappa B inhibition and Nrf2/heme oxygenase-1 activation signaling pathways, thus reducing the production of Th1 proinflammatory cytokines and cyclooxygenase-2 and inducible nitric oxide synthase overexpression.
Keywords: Fagaceae; HO-1; MAPKs; NF-κB; rf2; Quercus ilex; TNBS